Validation of telephone-based behavioral assessments in aging services clients. (20th September 2017) - Conwell, Yeates; Simning, Adam; Driffill, Nicole; Xia, Yinglin; Tu, Xin; Messing, Susan P.; Oslin, David
ABSTRACT: Background: The Behavioral Health Laboratory (BHL), a telephone-based mental health assessment, is a cost-effective approach that can improve mental illness identification and management. The individual BHL instruments, which were originally designed to be administered in-person, have not yet been validated with an in-person BHL assessment. This study therefore aims to characterize the concordance between the BHL data gathered by telephone and in-person interviews. Methods: A cross-sectional study was conducted with English-speaking aging services network (ASN) clients aged 60 years and older in Monroe County, NY who were randomized to a BHL interview either in-person ( n = 55) or by telephone ( n = 53). Results: There was strong evidence of equivalence between telephone and in-person interviews for depressive disorders, generalized anxiety, panic disorder, drug misuse, psychosis, PTSD, mental illness symptom severity, and five of the six questions assessing suicidality. There was marginal equivalence in PHQ-9 total scores and one of the six questions assessing suicidal ideation, and no evidence of equivalence between interview modalities for assessing cognitive impairment. Conclusions: With a few exceptions, the BHL gathered nearly equivalent information via telephone as compared to in-person interviews. This suggests that the BHL may be a cost-effective approach appropriate for dissemination in a wide variety of settings including the ASN. Dissemination of the BHL has the potential to strengthen the linkages between primary care, mental healthcare, and social service providers and improve identification and management of those with late-life mental illness.